2011
DOI: 10.1002/jnr.22755
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial transplantation of monocyte‐derived multipotential cells enhances recovery after ischemic stroke in rats

Abstract: Cell transplantation has emerged as a potential therapy to reduce the neurological deficits caused by ischemic stroke. We previously reported a primitive cell population, monocyte-derived multipotential cells (MOMCs), which can differentiate into mesenchymal, neuronal, and endothelial lineages. In this study, MOMCs and macrophages were prepared from rat peripheral blood and transplanted intracranially into the ischemic core of syngeneic rats that had undergone a left middle cerebral artery occlusion procedure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…This population originates from circulating CD14 + monocytes, and contains primitive cells that can differentiate into cells with the typical phenotypes and functions of mesenchymal cells, neurons, and endothelium in vitro [8][12]. We recently showed that the intracranial delivery of MOMCs enhances functional recovery in a rat model for ischemic stroke [13]. On the other hand, MOMCs derived from patients with systemic sclerosis were functionally altered and deficient in their ability to differentiate into endothelial cells, either in vitro or in vivo [14].…”
Section: Introductionmentioning
confidence: 99%
“…This population originates from circulating CD14 + monocytes, and contains primitive cells that can differentiate into cells with the typical phenotypes and functions of mesenchymal cells, neurons, and endothelium in vitro [8][12]. We recently showed that the intracranial delivery of MOMCs enhances functional recovery in a rat model for ischemic stroke [13]. On the other hand, MOMCs derived from patients with systemic sclerosis were functionally altered and deficient in their ability to differentiate into endothelial cells, either in vitro or in vivo [14].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several cultured human-cell populations originating from circulating monocytes have been reported. Those cultured monocytes have the capacity to differentiate into non-phagocytic pluripotent stem cell-like phenotypes and are named “pluripotent stem cells (PSCs)” [ 44 ], “monocyte-derived multipotential cells (MOMCs)” [ 45 47 ], or “programmable cells of monocytic origin (PCMOs)” [ 48 , 49 ]. As proof of pluripotency, cultured monocytes are reported to differentiate into epithelial-, endothelial-, hepatocytic-, pancreatic islet-, and neuronal-phenotype cells.…”
Section: Discussionmentioning
confidence: 99%
“…14 of the included studies delivered stem cells at 1 week or later after MCAo. 13 of these studies, including some in which stem cells were only administered 4 weeks after MCAo, reported an improvement in behavioral and/or histologic outcome [45,49,55,63,68,[70][71][72][73][74][75][76][77][78]. The other study did not report significant improvement in histologic outcome and even worsening of behavior was noted [62].…”
Section: Declarations Of Interestsmentioning
confidence: 99%